2019
DOI: 10.21608/assjm.2019.44132
|View full text |Cite
|
Sign up to set email alerts
|

Response of white maize hybrids to plant densities and nitrogen fertilizer rates

Abstract: Two field experiments were conducted on the Farm of Agric. Res. and Exp. Center of Fac. of Agric. Moshtohor, Benha University, Toukh Directorate, Qalyubia Governorate, Egypt, during the two successive summer growing seasons of 2016 and 2017 to study the effect of three plant population densities i.e. 20000, 24000 and 28000 plants/feddan (fed) and three nitrogen fertilizer rates, i.e. 90, 120 and 150 kg N/fed on the growth traits, yield components, yield and some kernels chemical properties of three white singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Similar results for this trait were reported by Turgut et al, (2005), Carpici et al, (2010), Baghdadi et al, (2012), Karashin (2014), Kumar et al, (2016). On the other hand, Mandic et al, (2015), Rahuma and muhumed (2018), El-Hosary et al, (2019), Fromme et al, (2019) and Li et al, (2019), reported that, plant height increased with increasing plant density, while, El-Mekser et al, (2009) and Awadalla and morsy (2016), reported that, plant height decreased with increasing plant density.…”
Section: Plant Characterssupporting
confidence: 81%
See 4 more Smart Citations
“…Similar results for this trait were reported by Turgut et al, (2005), Carpici et al, (2010), Baghdadi et al, (2012), Karashin (2014), Kumar et al, (2016). On the other hand, Mandic et al, (2015), Rahuma and muhumed (2018), El-Hosary et al, (2019), Fromme et al, (2019) and Li et al, (2019), reported that, plant height increased with increasing plant density, while, El-Mekser et al, (2009) and Awadalla and morsy (2016), reported that, plant height decreased with increasing plant density.…”
Section: Plant Characterssupporting
confidence: 81%
“…Number of leaves plant -1 varied among Egyptian maize hybrids as demonstrated by Awadalla and Morsy, (2016), El-Hosary et al, (2019) and Hegab et al, (2019). Also, international hybrids Mandic et al, (2015), Nwokwu (2016) and Nazly et al, (2019) reported similar results with other hybrid.…”
Section: Plant Charactersmentioning
confidence: 63%
See 3 more Smart Citations